2022
DOI: 10.1186/s40001-022-00674-3
|View full text |Cite
|
Sign up to set email alerts
|

Are anti-glutamic acid decarboxylase 65-kDa isoform antibodies related to diabetes or brain tumor?

Abstract: Background Antibodies against the 65-kDa isoform of glutamic acid decarboxylase (GAD65) are biomarkers of autoimmune disorders and are more common in non-neurological autoimmune diseases than in neurological disorders. As for the central nervous system (CNS), it is well known that GAD65 is primarily associated with stiff-person syndrome, cerebellar ataxia, epilepsy, and paraneoplastic neurological syndrome. However, GAD65 antibodies have not been reported in patients with brain tumors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…Although Gad65 positivity in our patient was associated with Diabetes Mellitus, it has been reported in the literature that Gad65 antibody may also be associated with cerebellar ataxia, epilepsy, brain stem syndromes, myelopathy, paraneoplastic neurological syndromes, and Gad65 may be associated with small cell or small cell lung cancer, lymphomas, neuroendocrine tumors and breast adenocarcinoma 13 . In addition, the literature has found that anti-titin antibodies can be associated with onconeuronal antibodies such as anti-Hu, Yo, Ri, Ma1, Ma2/Ta, CV2/CRMP5 and amphiphysin, which have been defined independently of myasthenia gravis, thymoma or thymic carcinoma.…”
Section: Casecontrasting
confidence: 54%
“…Although Gad65 positivity in our patient was associated with Diabetes Mellitus, it has been reported in the literature that Gad65 antibody may also be associated with cerebellar ataxia, epilepsy, brain stem syndromes, myelopathy, paraneoplastic neurological syndromes, and Gad65 may be associated with small cell or small cell lung cancer, lymphomas, neuroendocrine tumors and breast adenocarcinoma 13 . In addition, the literature has found that anti-titin antibodies can be associated with onconeuronal antibodies such as anti-Hu, Yo, Ri, Ma1, Ma2/Ta, CV2/CRMP5 and amphiphysin, which have been defined independently of myasthenia gravis, thymoma or thymic carcinoma.…”
Section: Casecontrasting
confidence: 54%
“…It is also associated with overlapping cancers, such as breast cancer with colon cancer ( 30 , 39 ), chronic lymphocytic leukemia ( 81 ), thymoma and non-Hodgkin lymphoma ( 80 ), non-functioning pituitary microadenoma, and endometrial cancer ( 29 ) ( Table 4 ). Table 5 shows the other carcinomas included in 25 studies involving six SPSSD subtypes, namely, classic SPS ( 21 36 ), SLS ( 86 , 90 ), PERM ( 91 ), progressive dizziness and unstable gait ( 87 ), and NMDAR-SPS ( 9 ). Furthermore, thyroid and renal cell cancers reportedly coexist with colon cancer and SPSSD ( 21 ).…”
Section: Clinical Characteristics Of Malignant Tumor-related Spssdsmentioning
confidence: 99%
“…The major SPSSD subtype is classic SPS ( 11 , 68 , 69 , 73 , 77 , 80 , 92 – 98 , 134 , 135 ), followed by SPS with myasthenia gravis ( 21 25 , 29 , 31 , 34 36 , 86 , 89 , 90 , 135 , 136 ), PERM ( 91 ), SLS ( 57 ), progressive dizziness and unstable gait ( 87 ), and NMDAR-SPS ( 9 ), as shown in Table 5 . Moreover, the major carcinoma associated with SPSSD subtypes is breast cancer ( 21 , 39 , 42 , 47 , 50 , 51 , 56 , 57 , 137 ), followed by thymoma ( 11 , 80 , 91 98 , 104 106 , 134 , 135 ), lymphoma ( 77 , 80 ), lung cancer ( 68 , 69 , 73 ), and other carcinomas ( 21 25 , 29 , 31 , 34 36 , 86 , 89 , 90 , 135 , 136 ).…”
Section: Possible Mechanisms Of Paraneoplastic Spssdmentioning
confidence: 99%
See 1 more Smart Citation